Synthesizing context for a sports domain on a mobile device - Devlic, Alisa; Koziuk, M.; Horsman, W. (Smart sensing and context : third European conference, EuroSSC 2008, Zurich, Switzerland, October 29-31, 2008 ; proceedings, 2008)
In ubiquitous computing environments there are an increasing number and variety of devices that can generate context data. The challenge is to timely acquire, process, and deliver these data to context-aware applications. The role of context synthesis is to generate new knowledge, as a result of a reasoning process applied to context information that is already present in the system. The success of this mechanism mainly depends on the response time that the end-user or an application must wait for the response to a context query. This paper describes and evaluates an approach to context synthesis on a mobile device to be used by a set of applications in a sports domain. A scenario based on a live race at the Super Prestige Cyclocross in Gieten, Netherlands demonstrates the use of context synthesis to dynamically compose gaps and groups of cyclists in order to provide a nearly real-time virtual ranking service.